Peningkatan Keterampilan Membaca Intensif untuk Penemuan Fakta dengan Penggunaan Teknik OPQRST pada siswa kelas VII-B SMPN 5 Sumenep Tahun Pelajaran 2016/2017 - Dwi Rahayu Lestari Rahayu lestari (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2021)
Improved Intensive Reading Skills for Fact Discovery with The Use of OPQRST Techniques in Grade VII-B Students of SMPN 5 Sumenep Year 2016/2017." The purpose of this research is to research the intensive reading skills of grade VII-B students of SMPN 5 Sumenep and research the improvement of intensive reading skills after using OPQRST techniques in grade V III students of SMPN 5 Sumenep. The method used by the research is class action research consisting of cycle I and cycle II. Each cycle consists of a stage of planning, execution of actions, observations, and reflections. The techniques used in this study are OPQRST techniques (overview, preview, question, research, summarize, and test). This research was conducted in February to The Month of M aret 2017 at SMPN 5 Sumenep. The data collection techniques used are interviews, observations, documentation, questionnaires, and tests. The results of this study are pretest value data, namely 54.23, cycle I with a value of 63.65, and cycle II with a value of 80.96. The student's response to this learning was very positive, seen from the improvements that occurred in the pretest, cycle I, and cycle II. The results prove that there is an increase in intensive reading skills for fact-finding with the use of OPQRST techniques in grade VII-B students of SMPN 5 Sumenep in the 2016/2017 school year.